The Relationship Between Knowledge and Practice Towards the Covid-19 Health Protocol of Students of SMPN 20 Dumai (Future Science, 2022)
According to the Joint Decree (SKB) of 4 ministers, the application of health protocols is an effective way to prevent the transmission of COVID-19 in schools. Beginning in 2022, face-to-face learning in schools has begun, and for that students' understanding of health protocols during face-to-face learning and vaccination will determine how to prevent COVID-19 in the school environment. This study aims to describe the knowledge and practice of the COVID-19 health protocols and vaccination at SMPN 20 students. A cross-sectional design with a purposive sampling technique and obtained a sample of 124 students was conducted. The instrument in this study used a validated research questionnaire. The results of this study showed the knowledge and practice of students on COVID-19 health protocol, as many as 79.8% of participants have been fully vaccinated status, and the knowledge and practice of students on COVID-19 vaccination, there was a significant relationship with the r result of 0.02. further, though students knew the benefits and side effects of vaccination, but were unable to understand or explain it well. The conclusion is that almost all students have good knowledge and practice regarding health protocols and vaccination. Though there was no significant relationship between student's knowledge and practice of the COVID-19 health protocol, there is a significant association between vaccination practices.